1989
DOI: 10.1073/pnas.86.20.8063
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine mechanism for v-sis transformation requires cell surface localization of internally activated growth factor receptors.

Abstract: ABSTRACTv-sis represents a prototype for the class of oncogenes that encode growth factors. Whether its plateletderived growth factor (PDGF)-like product functionally activates its receptors within the cell or at the cell surface has potential implications in efforts to intervene with the v-sistransformed phenotype. We demonstrate that intracellular as well as cell surface forms of two PDGF receptor gene products are tyrosine phosphorylated in v-sis transformants. In a chemically defred medium in which cell gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
62
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 38 publications
(35 reference statements)
7
62
0
Order By: Relevance
“…Pretreatment of the cells with suramin (100 MM) did not inhibit the induction of PDGF A-chain mRNA measured at either 6 or 18 h. Thus, suramin does not interfere with All-initiated signaling pathways leading to increased expression of PDGF-A mRNA in the RASM cells. These results are consistent with previous reports demonstrating that suramin, at concentrations that cause reversal of autocrine-stimulated cell growth, is not generally cytotoxic, and fails to inhibit cell growth ofseveral normal and tumor-derived cell lines (39,45 ). Taken together, these studies support the hypothesis that suramin inhibits an All-stimulated autocrine loop in RASM cells involving endogenously expressed growth factors.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Pretreatment of the cells with suramin (100 MM) did not inhibit the induction of PDGF A-chain mRNA measured at either 6 or 18 h. Thus, suramin does not interfere with All-initiated signaling pathways leading to increased expression of PDGF-A mRNA in the RASM cells. These results are consistent with previous reports demonstrating that suramin, at concentrations that cause reversal of autocrine-stimulated cell growth, is not generally cytotoxic, and fails to inhibit cell growth ofseveral normal and tumor-derived cell lines (39,45 ). Taken together, these studies support the hypothesis that suramin inhibits an All-stimulated autocrine loop in RASM cells involving endogenously expressed growth factors.…”
Section: Introductionsupporting
confidence: 83%
“…Suramin, a polysulfonated naphthylurea (for a review, see La Rocca et al [ 35 ]), has been shown to inhibit PDGF mitogenic activity and induce transient reversion of the v-sis-trans- formed phenotype in fibroblasts (36, 37). This antiproliferative activity appears to involve binding ofsuramin to PDGF, as well as displacement of bound PDGF from its receptors (37)(38)(39). Suramin also binds other growth factors such as basic FGF, acidic FGF, and IGF-I and interrupts binding to their respective high-affinity surface receptors (40)(41)(42).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of specific receptors is necessary for the ability to transform in response to PDGF. Thus, the constitutive production ofPDGF isoforms in tumor cells contributes to tumor cell growth through an autocrine mechanism (44)(45)(46)(47). Actually, a variety of neural crest-derived tumor cell lines including neuroblastomas, gliomas, and melanomas have been reported to express specific transcripts of PDGF genes and to produce PDGF-like molecules (33,48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover antibodies against PDGF in some instances revert the sis-transformed phenotype (54,55). The finding that suramin reverts the phenotype completely (50) but has no effect on the intracellular autophosphorylation of the receptor (48,51). is additional evidence against the model.…”
Section: The Sis Oncogene and Its Role In Autocrine Transformationmentioning
confidence: 65%
“…Thus, autophosphorylated receptors of the high-mannose form have been demonstrated in the interior of v-sis-transformed cells (48,49). Such receptors are not affected by suramin, in contrast to receptors activated at the plasma membrane by autocrine PDGF (50,51). Additional evidence for an intracellular activation has been derived from studies in which the sis-product has a transforming activity even when retained in the endoplasmic reticulum by a KDEL retention signal hooked to the C-terminal end of the mature B-chain (52).…”
Section: The Sis Oncogene and Its Role In Autocrine Transformationmentioning
confidence: 99%